HIV Infection and Circulating Levels of Prosurfactant Protein B and Surfactant Protein D. (19th December 2017) - Shiels, Meredith S; Kirk, Gregory D; Drummond, M Bradley; Dhillon, Dilsher; Hanash, Samir M; Taguchi, Ayumu; Engels, Eric A
Abstract : People with HIV manifest elevated serum levels of prosurfactant protein B compared to HIV-uninfected people, and levels are further increased in association with declining CD4 cell count, high HIV RNA, and in the absence of HIV treatment, independent of tobacco use. Abstract: Prosurfactant protein B (pro-SFTPB) and surfactant protein D (SFTPD) are markers of lung inflammation and damage. We estimated geometric mean pro-SFTPB and SFTPD levels in 500 human immunodeficiency virus (HIV)-infected and 300 HIV-uninfected injection drug users, adjusting for smoking and other covariates. Pro-SFTPB levels were significantly higher among people with HIV (PWH) (adjusted geometric mean, 21.4 vs 18.1 ng/mL; P = .03), and were higher with lower CD4 counts ( P trend = .001), higher HIV RNA ( P trend = .05), and without highly active antiretroviral therapy ( P = .03). These associations were not observed for SFTPD. Serum levels of pro-SFTPB are elevated among PWH and are associated with immunosuppression and uncontrolled viremia.